2010
DOI: 10.1016/j.jacc.2010.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ticagrelor Compared With Clopidogrel on Platelet Function in Patients With Acute Coronary Syndromes

Abstract: Ticagrelor achieves greater antiplatelet effect than clopidogrel in patients with acute coronary syndromes, both in the first hours of treatment and during maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
222
1
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 357 publications
(248 citation statements)
references
References 8 publications
(10 reference statements)
11
222
1
14
Order By: Relevance
“…We would like to underline that concomitant clopidogrel and antidiabetic drug use may significantly reduce therapeutic effect of clopidogrel. Ticagrelor is known for its fast onset [26], and has been shown to have greater antiplatelet activity compared with clopidogrel [27]. The PLATO study showed that ticagrelor is a more effective drug for the [2].…”
Section: Discussionmentioning
confidence: 99%
“…We would like to underline that concomitant clopidogrel and antidiabetic drug use may significantly reduce therapeutic effect of clopidogrel. Ticagrelor is known for its fast onset [26], and has been shown to have greater antiplatelet activity compared with clopidogrel [27]. The PLATO study showed that ticagrelor is a more effective drug for the [2].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in baseline characteristics were somewhat unexpected, as the drugs do not greatly differ from each other in terms of platelet inhibition. With the current approved maintenance dosing for both drugs, adequate levels of platelet inhibition 18 are achieved in over 90% of patients 11, 17, 19, 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…Более благоприятные клинические исходы при на-значении прасугрела или тикагрелора в сравнении с клопидогрелом у пациентов с ОКС с выполненным ЧКВ были убедительно продемонстрированы в 2 круп-ных рандомизированных клинических исследованиях (РКИ), соответственно TRITON-TIMI 38 и PLATO [20,21]. Их результаты стали основой для одобрения при-менения прасугрела и тикагрелора у этой категории больных в разных странах мира и включения их в ос-новные международные и российские рекомендации по лечению ОКС.…”
unclassified
“…Полученные в исследованиях TRITON-TIMI 38 и PLATO результаты по эффективности и безопасности прасугрела и тикагрелора крайне сложно сопоставлять между собой, так как существовали определенные раз-личия в популяции включенных пациентов и в дизайне исследований [20][21][22]. Терапия новыми блокаторами P2Y12-рецепторов в составе ДАТ ассоциировалась в обоих РКИ с лучшими клиническими исходами по сравнению с клопидогрелом.…”
unclassified
See 1 more Smart Citation